2016
DOI: 10.1097/ta.0000000000001080
|View full text |Cite
|
Sign up to set email alerts
|

The National Trauma Institute

Abstract: Lessons learned in the conduct of the first two funding rounds managed by NTI are instructive in four key areas: regulatory processes, multisite coordination, adequate funding, and the importance of an established research infrastructure to ensure study success. Recommendations for addressing institution-related and investigator-related challenges are discussed along with ongoing advocacy efforts to secure sustained federal funding of a national trauma research program commensurate with the burden of injury.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…National Trauma Research Action Plan will serve as the basis for federal advocacy efforts to support future trauma research funding. [42][43][44] AUTHORSHIP J.A.B., M.A.P., and E.M.B. contributed in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…National Trauma Research Action Plan will serve as the basis for federal advocacy efforts to support future trauma research funding. [42][43][44] AUTHORSHIP J.A.B., M.A.P., and E.M.B. contributed in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…The research agenda has momentum through the Coalition for National Trauma Research, a national nonprofit organization that addresses the funding shortage and coordination gap in trauma research. 19,20 Much of the funding has come through the Department of Defense, and there remains a need for coordinated support through the National Institutes of Health Institute for Trauma Research. The lack of recognition of traumatic injury as a public health problem continues to impact research funding.…”
Section: Trauma and The Emergency Care Systemmentioning
confidence: 99%
“…It has resulted in projects and created opportunities that will continue to be explored, and some have had momentum during the pandemic. The research agenda has momentum through the Coalition for National Trauma Research, a national nonprofit organization that addresses the funding shortage and coordination gap in trauma research 19,20 . Much of the funding has come through the Department of Defense, and there remains a need for coordinated support through the National Institutes of Health Institute for Trauma Research.…”
Section: Trauma and The Emergency Care Systemmentioning
confidence: 99%
“…In 2014, the National Trauma Institute, now known as the Coalition for National Trauma Research (CNTR), surveyed 16 federally funded investigators to identify facilitators and barriers to conducting trauma research. 4 Forty percent of the investigators reported challenges in obtaining regulatory approval. Several investigators encountered difficulties navigating the requirements for the Department of Defense (DoD) Human Research Protections Office (HRPO) approval processes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the National Trauma Institute, now known as the Coalition for National Trauma Research (CNTR), surveyed 16 federally funded investigators to identify facilitators and barriers to conducting trauma research 4. Forty percent of the investigators reported challenges in obtaining regulatory approval.…”
Section: Introductionmentioning
confidence: 99%